Effects of disorder and motion in a radical pair magnetoreceptor. - Lau, J; Wagner-Rundell, N; Rodgers, C; Green, N; Hore, P (2010)
A critical requirement in the proposed chemical model of the avian magnetic compass is that the molecules that play host to the magnetically sensitive radical pair intermediates must be immobilized and rotationally ordered within receptor cells. Rotational disorder would cause the anisotropic responses of differently oriented radical pairs within the same cell to interfere destructively, while rapid molecular rotation would tend to average the crucial anisotropic magnetic interactions and induce electron spin relaxation, reducing the sensitivity to the direction of the geomagnetic field. So far, experimental studies have been able to shed little light on the required degree of ordering and immobilization. To address this question, computer simulations have been performed on a collection of radical pairs undergoing restricted rigid-body rotation, coherent anisotropic spin evolution, electron spin relaxation and spin-selective recombination reactions. It is shown that the ordering and motional constraints necessary for efficient magnetoreception can be simultaneously satisfied if the radical pairs are uniaxially ordered with a moderate order parameter and if their motional correlation time is longer than about a quarter of their lifetime.